Borrowing from the palaeolimnologists toolkit; the use of lake sediment cores in diagnosing the causes of freshwater species decline - Robson, Hannah Jane; Jones, Vivienne Jane; Brooks, Stephen John; Sayer, Carl Derek; Douse, Andrew; Hilton, Geoff Mark (Frontiers in Conservation Science, 2023)
Populations of freshwater species are experiencing dramatic declines globally. Tools that facilitate the diagnosis of decline and identify management solutions and/or restoration targets are thus vital. Typically approaches taken to diagnose decline are carried out over short timescales and rely upon identifying spatial associations between presence or abundance of declining species and variables hypothesised to be driving decline. The potential to contextualise observed declines on longer time scales, with a broader range of potential explanatory variables is frequently dismissed, because of a perceived lack of existing long-term data. In this study we explore the value of incorporating a longer-term perspective to decline diagnosis using the common scoter as a case study. The number of scoter breeding in Scotland has declined substantially since the 1970s. Hypotheses for decline include a reduction in macroinvertebrate food available for females and young at the breeding lakes. In this study we apply palaeolimnological techniques to generate standardised, long-term ecological data, enabling us to characterise recent changes at four common scoter breeding lakes. Our results demonstrate that the (macroinvertebrate) food resource of common scoter has, in fact, gradually increased in abundance at all four sites from ca. 1900, and that a further statistically significant increase in macroinvertebrate abundance occurred at ca. 1970. We draw on our palaeolimnological data, to explore alternative hypotheses for common scoter decline. Increases in overall abundance across multiple algal, macrophyte and macroinvertebrate taxa, combined with specific increases in nutrient tolerant taxa, and concurrent declines in nutrient sensitive taxa indicate that the lakes have experienced enrichment within their current oligotrophic state during the last 100 years, and that this trajectory has become more marked during the period of common scoter decline. There is no evidence of changes to habitat, turbidity or increased competition from fish. In the absence of within lake changes that could be detrimental to the benthic (and generalist) feeding common scoter, we conclude that factors outside of the lake, such as increased predation, associated with afforestation in the surrounding area, are the most plausible drivers of common scoter decline. Prioritisation/testing of management solutions that address these issues are indicated.